What are the economic dimensions of occupational health and how should they be measured? A qualitative study - Nathanael Lutz; Lena Dalle Grave; Dirk Richter; Tom Deliens; Nick Verhaeghe; Jan Taeymans; Peter Clarys (BMC Public Health, 2022)
Abstract Background Decision makers want to know if there is a financial benefit in investing scarce resources in occupational health management (OHM). Economic evaluations (EEs) of OHM-strategies try to answer this question. However, EEs of OHM-strategies which are strongly marked by quantitative methods may be limited by contextual, qualitative residuals. Therefore, the objectives of this study were to (1) explore important economic dimensions of OHM and (2) to discuss the methods used in current EEs for measuring these dimensions. Methods In this explorative qualitative study, OHM-specialists were recruited via the Swiss organisation for health promotion. Thirteen semi-structured interviews were performed from November 2020 until May 2021. Videotapes were transcribed verbatim and organised by using an open coding strategy. Codes were clustered and synthesised as themes (i.e. the dimensions of EEs of OHM) through a mix of inductive and deductive content analysis. Member check with eight participants was accomplished to validate the results. Results The interviews had an average duration of 70.5 min and yielded 609 individual codes. These codes were merged into 28 subcategories which were finally categorised into five main themes: Understanding of OHM, costs, benefits, environmental aspects, and evaluation of OHM. Participants stated that the greater part of costs and benefits cannot be quantified or monetised and thus, considered in quantitative EEs. For example, they see a culture of health as key component for a successful OHM-strategy. However, the costs to establish such a culture as well as its benefits are hard to quantify. Participants were highly critical of the use of absenteeism as a linear measure of productivity. Furthermore, they explained that single, rare events, such as a change in leadership, can have significant impact on employee health. However, such external influence factors are difficult to control. Conclusions Participants perceived costs and benefits of OHM significantly different than how they are represented in current EEs. According to the OHM-specialists, most benefits cannot be quantified and thus, monetised. These intangible benefits as well as critical influencing factors during the process should be assessed qualitatively and considered in EEs when using them as a legitimation basis vis-à-vis decision makers.